Interacting Croatian NERC System and Intex/NooJ Environment - Bekavac, Božo (Array, 2010)
In this contribution, we present design and implementation details of an early version of Croatian finite state transducer engine called NercFst. The engine currently implements a small subset of Intex/NooJ finite state transducer functionality developed for the purpose of deriving a standalone module for named entity recognition and classification (NERC) system applicable to Croatian texts, previously created as a module in Intex. We also provide some general notes on the Intex module for Croatian NERC and notes on porting the module from Intex to NooJ. Current NercFst engine functionality overview is given in more detail along with some upcoming export features for NooJ which are currently under development with a purpose of supporting portability to various other open source finite state transducer libraries by exporting systems designed and implemented within Intex or NooJ linguistic development environment.